2022
DOI: 10.4236/aim.2022.122005
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Pattern and Identification of Multidrug Resistant Novel <i>Salmonella</i> Strain in Poultry Chickens of Hathazari Region in Chattogram, Bangladesh

Abstract: Poultry chickens are potential source of transmission of zoonotic Salmonella, into human food chain, causing food-borne illness and also hindering development of poultry industry in Bangladesh. The non-judicious uses of antibiotics in poultry farm have increased the multidrug resistant bacteria. So, this study reports the occurrence of Salmonella in poultry samples (meat, egg, liver and cloacal swab) and the antimicrobial resistance pattern of the isolates. This study was carried out throughout the period of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…Meanwhile, low resistance was recorded with DO, SXT, FFC (46.15%, for each) and N (30.77%). These findings were in near similarity with those of Hardiati et al 38 , who reported that Salmonella isolated from chicken farms was resistant to OT and ampicillin (AM) with (75%), Islam et al 39 , who showed resistance against AM (75%), N (50%) and DO (50%). Meanwhile, Velasquez et al 36 recorded a higher resistance of Salmonella isolates against S, and Alam et al 40 recorded resistance against AM and S of 82.85% and 77.14%, respectively.…”
Section: Discussion/conclusionsupporting
confidence: 87%
“…Meanwhile, low resistance was recorded with DO, SXT, FFC (46.15%, for each) and N (30.77%). These findings were in near similarity with those of Hardiati et al 38 , who reported that Salmonella isolated from chicken farms was resistant to OT and ampicillin (AM) with (75%), Islam et al 39 , who showed resistance against AM (75%), N (50%) and DO (50%). Meanwhile, Velasquez et al 36 recorded a higher resistance of Salmonella isolates against S, and Alam et al 40 recorded resistance against AM and S of 82.85% and 77.14%, respectively.…”
Section: Discussion/conclusionsupporting
confidence: 87%
“…Antibiotic resistance can develop as a result of excessive antibiotic usage [ 3 , 42 , 43 ]. In this study, the antimicrobial resistance profile among Salmonella isolates was nearly similar to those recorded in Egypt [ 6 ], China [ 44 ], and Bangladesh [ 31 ].…”
Section: Discussionsupporting
confidence: 76%
“…In the current study, the prevalence rate was 10% which is consistent with previous studies by Ammar et al [ 28 ] and Ibrahim et al [ 29 ] in Egypt. However, a relatively higher isolation rate of 35.9% was observed in Ethiopia by Berihun et al [ 30 ] and 37.5% in Bangladesh [ 31 ]. On the other hand, Helmy et al [ 32 ] recorded a lower percentage of 3.4% from apparently healthy chickens in Egypt.…”
Section: Discussionmentioning
confidence: 99%